Development of a Smartphone-Based Digital Reporting System to Optimize Radiation Safety Reporting in the Radiation Oncology Facility - Elzar, Andri; Dian Pratiwi, Rita; Dharmastiti, Rini; Kusuma Frisky, Aufaclav Zatu (Rifa'Institute, 2026)
Introduction: Radiation safety reporting at the Radiation Oncology Facility of RSUD Dr. H. Abdul Moeloek was still paper-based, causing incomplete data, delayed reporting, and fluctuating Safety and Security Indicator (IKK) scores. Objective: This study aimed to develop and evaluate a smartphone-based digital reporting application to improve radiation safety reporting and safety culture. Method: This Research and Development study used the ADDIE model with mixed qualitative and quantitative approaches. The application was developed using the AppSheet low-code platform and validated by practitioners and media experts. Evaluation applied a one-group pretest-posttest design involving 30 radiation workers. Data were analysed using regression, paired t-test, and correlation analyses. Results and discussion: The SPEKTRA application achieved a validation score of 94.5% and was categorized as highly feasible. Post-implementation results showed significant improvements in perceived ease of use, perceived usefulness, intention to use, and safety culture (p < 0.001). Perceived usefulness was the dominant predictor of intention to use (β = 0.473; p = 0.022). Application adoption also significantly improved safety culture (p = 0.034). The projected IKK score increased from 75 in 2025 to 94 in 2026 through the integrated simulation feature. Conclusion: SPEKTRA effectively improved technology acceptance, safety culture, and radiation safety reporting management.